The origin of pharmacology and the evolution from apothecaries to pharmacies in the story «¡A nadar, peces!» - Ibarra Bringas, Jesús Jessup (2022)
This article will analyze the story «¡A nadar, peces!», by Ricardo Palma. This story describes the empirical knowledge of the apothecary, as well as how apothecaries' shops functioned in Peru during the Viceroyalty. The main source of information for the research will be the pharmacopeia, a text that compiles recipes for medicinal products, as well as other sources that allow us to study the origin and development of pharmacology in Peru.